GEOMORPHOLOGICAL ANALYSIS OF THE SUKAMULYA AND SURROUNDINGS AREA, LANGKAPLANCAR AND CIGUGUR DISTRICTS, PANGANDARAN REGENCY, WEST JAVA PROVINCE - Ryonaldo Rizqi, Muhammad Ibrahim; Iskandarsyah, T. Yan Waliana Muda (Universitas Padjadjaran, 2026)
Geographically, the Sukamulya and surroundings area, Langkaplancar and Cigugur subdistricts, Pangandaran Regency, West Java Province, are located at 108°30'9.44” E to 108°32'51.343” E and 7°33'42.896” S to 7°36'23.595” S. This study area is located in the South Mountain Zone of West Java, which is characterized by hilly relief and strong tectonic and volcanic influences. This study aims to identify geomorphological conditions and understand their formation processes based on morphographic, morphometric, and morphogenetic approaches. The research methods included spatial analysis or remote sensing using National Digital Elevation Model (DEMNAS) data and validation through geomorphological observations in the field. Several parameters were analyzed, including landform, river flow patterns, slope inclination, lithology, and the influence of geological structures. The results show that the study area is dominated by hills with altitudes between 115 and 436 meters above sea level and slope gradients ranging from 13 to 55%. The drainage patterns that developed were rectangular and subparallel, indicating the control of geological structures and slope inclination on the development of the drainage system. The geomorphological characteristics in the study area were divided into three units, namely the Slightly Steep Structural Hills Unit, the Steep Structural Hills Unit, and the Steep Volcanic Hills Unit. Generally, landscape forming in the study area is controlled by the interaction of endogenous processes such as tectonic activity and volcanism, as well as exogenous processes such as erosion and weathering. This study provides to contribute to the fields of geology and geomorphology, serve as a basis for land use planning, and inform further studies on potential geological hazards such as landslides.